Impacts of social distancing from the COVID-19 pandemic on older people with Alzheimer's: Scoping review (Research, Society and Development, 2024)
Aim: To map the impacts of social distancing measures adopted during the COVID-19 pandemic for elderly people diagnosed with Alzheimer's Disease. Methodology: Scope review according to the JBI method. The search strategy was applied and adapted in the databases LILACS and others/VHL, Scopus and Embase/Elsevier, MEDLINE/PUBMED, CINAHL and others/Ebsco, Cochrane Library/Wiley, PsycINFO/APA and Web of Science Core Collection/Clarivate and on Google Scholar. The Rayyan system was used to manage the selection of the papers. The extraction was carried out using a data extraction instrument designed to achieve the objective of this review. Results: The search resulted in 25 studies and six main themes were identified: impacts on cognition; impacts on behavioral and psychological symptoms of dementia; impacts on functionality; impacts on access to health care services; impacts on quality of life and impact on stress levels. Conclusion: The results indicate the need for changes in the care paradigm that was adopted during the last pandemic, as elderly people with Alzheimer's were affected by social distancing measures in several areas. The development of more flexible care management, adapted to the specific needs of this group, can be a powerful strategy both to avoid the suspension of cognitive/physical stimuli and to promote some level of sociability for people with AD, as well as to maintain assistance to their caregivers during pandemic scenarios.